(untitled) (Ameghiniana, 2014)
A right fragmentary ramus with p4 - m3 cardiatherin rodent is described.r It comes · from the paralic sediments of the Ituzaing6 Formation ("Mesopotamian") from Entre Rios Province. Based on its size and on the characteristics of p4 - m3 it is assigned to Kiyutherium scillatoyanei sp. nov. The presence of a cardiatherin rodent would indicate enviromental conditions of flood plains with !otic and lentic aquatic bodies, grasslands and also probably wooded areas.